Moringa oleifera: A review on nutritional attributes, therapeutic applications and value-added product generation: A review on nutritional attributes of moringa oleifera - Ali, Md Younus; Khalil, Md Ibrahim; Jahan, Fatema Nasrin; Hossain, Md Baktear; Samanta, Ashis Kumar (SAARC Journal of Agriculture, 2022)
Moringa oleifera, a perennial tree of Indian origin, is cultivated in several tropical and sub-tropical countries because of its ability to grow under unfavourable conditions such as poor soil, lower requirement of water and managemental practices. The leaves and pods of the plant are highly rich in essential nutrients such as protein, vitamin, essential amino acids, macro and micro elements in addition to the presence of diverse nutraceutical molecules such as antioxidant, flavonoids, isothiocyanates, phenolics etc. The presence of bioactive principles in different parts of the Moringa plant prompted the people to use it as part of traditional medicines for the cure of several human ailments such as diabetes, intestinal worms, hyperlipidaemia, high blood pressure, muscle spasm, constipation, ringworm, etc. With the growing health consciousness coupled with phobia against modern chemical based therapeutic, there is increasing demands for plant sourced nutraceuticals. Evidently, this gives opportunity for development of Moringa based product for welfare of human society. The current review made an effort to summarize the research advancement on different aspects of Moringa oleifera focussing on taxonomy, cultivation, nutritional attributes, therapeutic values, and value-added products of this divine tree. SAARC J. Agric., 20(2): 1-15 (2022)